FENO AND ATOPY IN PEDIATRIC ASTHMA - Cristiana Stanciulescu; Mirela Chiru; Alina Oprea; Daniela Pacurar; Carmen Zapucioiu; Elena Petrisor; Dumitru Oraseanu (Romanian Journal of Pediatrics, 2015)
Objectives. The aim of this study was to determine the manner in which the level of exhaled nitric oxide (FENO) infl uences the atopic status in children with asthma. Methods. The study included 92 asthmatic children (aged 5-18 years) admitted on the Pediatric Clinic of “Grigore Alexandrescu” Emergency Clinical Hospital for Children. The atopic status was evaluated through anamnesis, clinical examination and laboratory determination of serum eosinophils and total Ig E. All children underwent measurement of FENO. Results. Children with atopic asthma had higher levels of FENO than children with nonatopic asthma. The FENO values correlate with eosinophilia and high values of immunoglobulin E. Conclusion. FENO is a useful marker for the evaluation of airway infl ammation in children with atopic asthma.